Fairy tales and moral values: a corpus-based approach. - Silva, Rafael Silveira (BELT - Brazilian English Language Teaching Journal, 2012)
The purpose of this article is to carry out a corpus-based study on the presence of moral values in a selection of ten summarized online version of the tales (Snow-white and the seven dwarfs, The three little pigs, Cinderella, The sleeping princess, The Adventures of Aladdin, Beauty and the beast, The ant and the cricket, Prince Omar and Princess Scheherazade, Little Red Riding Hood, The Ugly Duck) by the Grimm’s Brothers by looking at the terms which can be said to relate to the above mentioned semantic field. More specifically, this study will investigate the frequency and usage of the words love, little and girl. These words have been chosen due to their possible connection to moral values after checking the word frequency list of the whole corpus. The study initially involved the analysis of frequencies of words in the Brothers’ Grimm corpus and, secondly, a comparison of the results with The Contemporary American English Corpus (Coca). The software used to analyze the data in Grimm’s corpus was AntConc 3.2.4.